Model Transmisi Keilmuan dalam Peradaban Islam Abad Pertengahan dan Kontribusinya terhadap Pengembangan Pendidikan Islam Kontemporer - Muh Khaidir Firmansyah Bialangi; Zahro Tunisa Pakaya; Muh Faisal Dunggio; Musdalifah Lamarunga; Chaterina P. Doni (CV MUARA EDUKASI, 2026)
Contemporary Islamic education faces a range of challenges, including the weakening of academic culture, the dichotomy of knowledge, the decline of literacy traditions, and the diminishing pedagogical relationship between teachers and students. These challenges highlight the need to revisit the Islamic intellectual traditions that once served as the foundation of the flourishing Islamic civilization. This study aims to analyze the model of knowledge transmission in medieval Islamic civilization, identify the factors that contributed to its success, and examine its contribution to the development of contemporary Islamic education. Employing a qualitative approach through library research, this study analyzes various primary and secondary sources related to the classical Islamic educational tradition. The findings reveal that the model of knowledge transmission in medieval Islamic civilization was established through interconnected systems of sanad (chains of transmission), halaqah (study circles), talaqqi (direct learning from teachers), scholarly journeys (rihlah ilmiyyah), ijazah (academic authorization), literacy culture, and networks of scholars, all supported by educational institutions such as mosques, madrasahs, libraries, and centers of learning. This system not only ensured the continuity of knowledge but also fostered character development, academic ethics, and intellectual integrity. The study further demonstrates that the values embedded within the classical Islamic knowledge transmission model remain highly relevant for strengthening academic integrity, participatory learning, character education, academic mobility, and the integration of knowledge in the development of contemporary Islamic education.